Plain Photo Overview of Legg Calve Perthes Disease - Anggita Putri Kantilaras (International Journal of Health and Pharmaceutical (IJHP), 2026)
Legg-Calvé-Perthes disease (LCPD) is a condition affecting the hip joint in children, characterized by avascular necrosis of the femoral head due to impaired blood flow. The disease primarily affects children aged 2–8 years, with a higher incidence in males. The exact cause of the disease remains unknown, but potential factors include trauma, vascular compromise, and coagulation abnormalities. LCPD is diagnosed through clinical symptoms, physical examination, and imaging, with plain radiographs being the primary diagnostic tool. The disease progresses through four stages: ischemia, fragmentation, rheoossification, and remodeling, each with characteristic radiographic features. In the early stages, plain radiographs are often normal, which can lead to misdiagnosis. Treatment aims to prevent arthritis and deformity, with conservative approaches such as physiotherapy or surgical intervention depending on the severity and age of the patient. This review aims to provide an overview of the radiographic features and clinical stages of LCPD, emphasizing the importance of early detection for more effective management and improved outcomes.